2015
DOI: 10.1016/j.jenvman.2014.11.035
|View full text |Cite
|
Sign up to set email alerts
|

The release of As, Cr and Cu from contaminated soil stabilized with APC residues under landfill conditions

Abstract: The aim of this study was to investigate the stability of As, Cr and Cu in contaminated soil treated with air pollution control residues under landfill conditions. The influence of landfill gas and temperature on the release of trace elements from stabilized soil was simulated using a diffusion test. The air pollution control residues immobilized As through the precipitation of Ca-As minerals (calcium arsenate (Ca5H2(AsO4)3 × 5H2O), weilite (CaAsO4) and johnbaumite (Ca5(AsO4)3(OH)), incorporation of As into et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The sample was scanned for 16 h with a step size of 0.0334 0 from 0 to 100 0 at room temperature. Spectra collected by Ferreira, Travar, Hamdan and Alawadhi (Ferreira et al, 2006;Travar et al, 2015;Hamdan and Alawadhi, 2020) were used as a reference.…”
Section: Physico-chemical Imaging and Analyses Of The Pmmentioning
confidence: 99%
“…The sample was scanned for 16 h with a step size of 0.0334 0 from 0 to 100 0 at room temperature. Spectra collected by Ferreira, Travar, Hamdan and Alawadhi (Ferreira et al, 2006;Travar et al, 2015;Hamdan and Alawadhi, 2020) were used as a reference.…”
Section: Physico-chemical Imaging and Analyses Of The Pmmentioning
confidence: 99%
“…Immobilisation is one of the conventional methods used to treat metal(loid)-contaminated soils, and among other immobilising agents such as P compounds and Fe or Mn oxides, materials rich in Ca are also being used (Bolan et al 2014 ). As reported by Travar et al ( 2015 ), the formation of poorly soluble Ca-As minerals such as calcium arsenate, weilite and jahnbaumite were responsible for the immobilisation of As in the contaminated soil, where a Ca-rich waste product derived from the air pollution controller in an incinerator was added. In the same study, it was reported that the addition of Ca had a slight mobilising effect on Cr and Cu.…”
Section: Introductionmentioning
confidence: 68%
“…There is thorough lab-scale research on chemical soil washing using a variety of leaching agents, including inorganic acids, bio surfactants and complexing agents such as EDTA or its derivates [2][3][4][5][6][7][8]. Apart from cases where water was used as the leaching agent, not many pilot scale experiments have been conducted [9]. A reason might be that when virgin chemicals are used, recirculation or reuse of the leaching agents is essential in order to ensure an efficient and economically viable process.…”
Section: Introductionmentioning
confidence: 99%